A longitudinal study of cortical grey matter lesion subtypes in relapse-onset multiple sclerosis. Issue 7 (13th August 2015) - Sethi, Varun; Yousry, Tarek; Muhlert, Nils; Tozer, Daniel J; Altmann, Daniel; Ron, Maria; Wheeler-Kingshott, Claudia; Miller, David H; Chard, Declan T
Abstract : Background: Cortical grey matter (GM) lesions are common in multiple sclerosis (MS), but little is known about their temporal evolution. We investigated this in people with relapsing–remitting (RR) and secondary progressive (SP) MS. Methods: 27 people with RRMS, and 22 with SPMS were included in this study. Phase-sensitive inversion recovery scans were acquired on 2 occasions. Cortical GM lesions were classified as intracortical (IC, only involving GM) and leucocortical (LC, mixed GM–white matter (WM)); WM lesions touching the cortex as juxtacortical (JC). On follow-up scans, new IC, LC and JC lesions were identified, and any change in classification of lesions previously observed was noted. WM lesion counts in the whole brain were assessed on PD/T2-weighted scans. Results: Over a mean (SD) of 21.0 (5.8) months, the number of new IC lesions per person per year was greater in SPMS (1.6 (1.9)) than RRMS (0.8 (1.9)) (Mann-Whitney p=0.039). All new LC lesions arose from previously seen IC lesions (SPMS 1.4 (1.8) per person per year, and RRMS 1.1 (1.0)), and none arose de novo, or from previously seen JC lesions. Changes in cortical GM (either new IC or IC converting to LC) lesion counts did not correlate with the changes in WM lesion counts. Conclusions: New cortical GM lesions rarely arise from the WM and the rate of new IC lesion formation is not closely linked with WM lesion accrual. IC lesion formation appears to be more common in SPMS than RRMS.